The Position of Village-Owned Enterprises in Improving Community Welfare in The Field of Basic Education - Muhamad Ajwar; I Nengah Suastika; Ferniawan, Ferniawan (JURNAL PENDIDIKAN IPS, 2023)
Village-owned enterprises are built not only to function in economic business but also to work in the field of learning as an effort to meet the needs and welfare of villagers. The business of having a village engaged in learning is no less meaningful as other field businesses. The goal is to find out the position of village-owned enterprises in improving the welfare of residents in the field of basic education, as well as to recognize what other business fields are carried out by village-owned enterprises in Wera sub-district. This type of research is descriptive qualitative. The instrument used in collecting information is in the form of an interview instrument. Information analysis begins with reduction information, display information and conclusion drawing verification. Information is also analyzed using a percentage formula. The results of the study proved that the majority of businesses run in the field of savings and loans with a percentage of 57%, Angkringan Business with a percentage of 14%, Livestock and agriculture with a percentage of 29%. in education with a percentage of 0%. It can be concluded that village-owned enterprises do not have a position in the field of education, it is stated in the study that village-owned enterprises do not have a position in the field of education, including basic education.